School Starting Age and Academic Performance: An Empirical Study in Indonesia - Fawina Aulia Guswandi (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2021)
School entry regulations in Indonesia have a specific cutoff date for enrolment and it requires children to start school at the age of seven. In practice, there were schools that allowed children to start elementary school before reaching seven years old. This might create age differences between children in the same grade at school. Some literature has been shown that older students outperform younger students in the school outcomes. For instance, higher education attainment, reduce grade repetition, and excellent academic performances. However, limited evidence exists about the school starting age and academic performances in Indonesia. In order to determine whether the school starting age rule in Indonesia affects children’s academic performance, this study utilizes the Indonesian Family Life Survey (IFLS wave) 5 and regression discontinuity design. This study found that older entrance might get lower score compared to the children who start school at early age. Based on the results, entering school earlier might increase the average of total score by 2.687 grade points higher than older entrance.